Strategies to Overcome Failures in T-Cell Immunotherapies by Targeting PI3K-δ and –γ - Chandrasekaran, Sanjay; Funk, Christopher Ronald; Kleber, Troy; Paulos, Chrystal M.; Shanmugam, Mala; Waller, Edmund K. (Frontiers in Immunology, 2021)
We examine an exciting new role for using isoform selective PI3K-δ and/or PI3K-γ inhibitors as T-cell immunomodulators in combination with cancer immunotherapies. PI3K-δand PI3K-γ are critical regulators of T-cell differentiation, senescence, and metabolism. Additionally, PI3K-δand PI3K-γ signaling can contribute to T-cell inhibition via intrinsic mechanisms and regulation of suppressor cell populations, including regulatory T-cells and myeloid derived suppressor cells in the tumor. Herein we review the current literature on the implications of PI3K-δ and -γ inhibition in T-cell biology, discuss existing challenges in adoptive T-cell therapies and checkpoint blockade inhibitors, and highlight ongoing efforts and future directions to incorporate PI3K-δand PI3K-γ as synergistic T-cell modulators in immunotherapy.